Research on the impact of exchange rates and interest rates on carbon price changes in the context of sustainable development - Yang, Jiajun; Wan, Yuzhu; Shen, Songdong (Frontiers in Ecology and Evolution, 2023)
Carbon emissions are closely linked to a company's production activities. The amount of carbon allowances a company holds determines its carbon emissions. Changes in carbon prices interact with firms' production activities, while changes in exchange rates and interest rates have a direct impact on firms' production structure, willingness to produce and scale of production. Under the existing literature, most scholars have selected only one market to be used to study its influence on the carbon market. This paper is innovative and comprehensive in its selection of exchange rate markets and interest rate markets to study the influence of both on the carbon market, as well as enriching the theory in this area and suggesting useful countermeasures based on the results of the study. The empirical results show that interest rates are positively linked to carbon prices, while exchange rates are more negatively linked to carbon prices; exchange rates are less affected by macro factors and external shocks, while interest rates are the opposite and very sensitive to macro shocks; under the training and simulation of the neural network, carbon prices can fluctuate drastically under the combined influence of exchange rate and interest rate movements, which can provide appropriate early warning of future price fluctuations in carbon trading. This shows that adjustments to exchange rates and interest rates need to be treated with caution, and appropriate adjustments should be made to keep carbon prices stable; the government should build a mechanism to transform the green development of enterprises, pushing them to save energy and reduce emissions to achieve low-carbon transformational development; the government should not only introduce policies to support low-carbon enterprises, but also improve the national carbon market laws and regulations and price regulation mechanisms.